Take Charge of Your Career-Career Development - Annabelle Reitman, Ed. D. (Association for Talent Development, 2003)
Whether you need a career check up or you are actively seeking a new career or employment, this Infoline may be your ticket. This issue provides tips and tools to understand your personal and professional needs, prepare and execute a career move, or just survive the search for a new job. You will find a sample resume along with checklists on setting professional priorities, informational interviewing, resume tips, and a job search, marketing campaign action plan job aid.